Microalgae as alternative proteins for the sustainable food industry: A review - E. Son; K. H. Kwon (Теория и практика переработки мяса, 2023)
This paper reviews the nutritional properties and consumer perceptions of microalgae foods through various recent studies on alternative protein sources. Food choices, including meat consumption, are a common concern for humanity. Thus, we focused on whether microalgae foods have a sufficient value as a protein source and what nutritional benefits they have. Based on existing papers, we conducted a systematic review using Web of Science, Google Scholar, and Scopus to comprehensively investigate and summarize the nutritional characteristics of microalgae, sustainable diets, and awareness of microalgae as an alternative protein source. Research has shown that microalgae have been consumed by humans as a protein source since ancient times, and contain enough protein to be used as an alternative protein source. They also have many other nutritional benefits, such as vitamins. We have found that consumers are increasingly interested in alternative protein sources, and the more they learn about microalgae, the more accepting they become. These results may suggest a need for further research to improve microalgae as an alternative protein source in the long run and develop them into a variety of foods.